Surveyor and dasawisma training in housing database collection in Bukit Duri Village - Inavonna Inavonna; Wahyu Sejati; Darmawan Pontan; Avelina Nathania Bennediktus Suhardjo Pusoko (Community Empowerment, 2024)
Nestled within Tebet District, South Jakarta, Kelurahan Bukit Duri stands as a densely populated area, encompassing 108 hectares and home to 28,151 residents. This community empowerment initiative sought to empower university students as surveyors and community women (dasawisma) as survey assistants by equipping them with the necessary knowledge and skills. Through comprehensive training sessions, participants delved into the intricacies of building reliability assessment, the effective utilization of survey platforms, and communication strategies for conducting surveys. The program's impact was evident in the remarkable improvement in the empowerment and understanding of both surveyors and dasawisma. Prior to the training, their comprehension level stood at 30%, but upon completion, it surged to an impressive 90%. This program is poised to minimize errors during structural assessments, ensuring the safety and well-being of Bukit Duri's residents.